Biological (circadian) rhythms rating to study elite athletes' adaptability in extreme environments - Koryagina, J. V.; Ter-Akopov, G. N.; Nopin, S. V.; Roguleva, L. G. (Theory and Practice of Physical Culture, 2018)
Objective of the study was to rate the circadian (circadian) biological rhythms in elite athletes in different competitive processes and special environmental (middle altitude) conditions. The study data and analysis found expressed circadian rhythms in the heart rate of the elite athletes in the periods of the term hypoxic adaptation in the middle altitude environments under heavy physical workloads. Tense adaptation processes in the athletes rated by deviations of the physical working capacity rates from the norms were found to affect the rhythm amplitude and mesors without disorders in the physiological process rhythms in the middle altitude adaptation period. Athletes with the lower blood pressure rates are tested with the lower mesors and amplitudes of the HR circadian rhythm; and the athletes diagnosed with highly tensed control mechanisms are tested with the high rhythm amplitudes and mesors.